The reality of middle school teachers in Arar, Saudi Arabia, applying the flipped classroom strategy - Alanazi, Abdulaziz Eid bin Nazzal (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the reality of middle school teachers applying to the flipped classroom strategy. To achieve the objectives of the study, the researcher used the descriptive survey method, and prepared the study tools to collect data, which is (the questionnaire) and included (44 items), applied to a sample of middle school teachers in Arar; their number reached (194) teachers, (and the interview) and included (18) a paragraph). It was applied to (23) educational supervisors who supervise the middle stage, and they represent the full study community. After analyzing the results statistically, the study reached the following results: The reality of middle school teachers in the city of Arar, Saudi Arabia, of the flipped classroom strategy got a total average (3.99 out of 5), with a (large) estimate and at the axis level, the reality of middle school teachers' knowledge of the flipped classroom strategy got an average (4.24) with an estimate (very large) , Followed by the axis of the degree of application of the teachers of the middle stage of the flipped classroom strategy with an average of (3.93) and finally the axis of the difficulties of implementing the flipped classroom strategy with an average of (3.81), both of which are (large). The results also showed the absence of statistically significant differences at the level of (α≤0.05) between the responses of the intermediate stage teachers in the application of the flipped classroom strategy in Arar, according to the difference in the educational qualification (diploma - Bachelor - Master - PhD), as well as according to the variable (years of experience). Based on the results, a number of recommendations and proposals were presented to train teachers and activate the flipped classroom strategy.
Keywords: application; Middle school teachers; Arar City; Flipped classroom strategy